Join the conversation : how to engage marketing-weary consumers with the power of community, dialogue, and partnership - Jaffe, Joseph, 1970- (Hoboken, N.J. : John Wiley & Sons, 2007)
With the continued fragmentation of the media and proliferation of media options, the balance of power has shifted from the marketer to the individual. In Join the Conversation, Jaffe discusses the changing role of the consumer and how marketers must adapt by joining the rich, deep and meaningful conversation already in progress. This book reveals what marketers must do to become a welcome and invited part of the dialogue, and how to leverage and integrate the resulting partnership in ways that provide win-win situations for businesses, brands and lives.
Talking "at" versus talking "with" -- The many-to-many model -- Can marketing be a conversation? -- The birth of generation i -- The rise of the prosumer -- The new consumerism -- The six Cs: three phases of conversation -- The content-conversation relationship -- What conversations are in your future? -- Why are you so afraid of conversation? -- The ten tenets of good conversation -- The five ways you can join the conversation -- When conversation isn't conversation at all -- Where does conversation fit in? -- Conversation through community -- Conversation through dialogue -- Conversation through partnership -- Getting started: the manifesto for experimentation -- Does conversation work? -- Do you speak conversation? Take the test.
"Published simultaneously in Canada."
Includes bibliographical references and index.
Keywords: Business communication; Customer relations; Marketing; Relationship marketing